Некоторые задачи управления групповым движением подвижных роботов - Кунцевич, В. М. (Видавництво Львівської політехніки, 2011)
The problem of motion control of a group of mobile robots consists of two separate problems: statement of the objectives and the mission carried out by a group of robots, and its implementation. This kind of decomposition of the motion control problem for a group of robots determines the hierarchical structure of a control system. Implementation of the given program of motion is put on local control systems for each individual robot.
Keywords: Группа подвижных роботов; конфигурация группы